Assesment of port governance in Brazil: a managerial perspective on the port of Santos - Almeida, José Eduardo Costa de (2015)
The role of maritime transportation within international trade was drastically revamped during the inception of the globalization process, which enhanced the contribution of ports in world economy as main logistics gateways for global production and trade. As a result, the relationship between ports and governments has changed. Devolution ideologies that had been applied in other industries decades ago were now being considered by governments for the port industry. Many central governments sought to extract themselves from commercial activities of ports and devolving this responsibility to local governments, communities or private entities. The institution of devolution programs also changed the governance structures of ports further influencing port performance. Consequently, the recent worldwide trend towards devolution in the port industry has spawned considerable variety of governance models that are now set in place around the world. While some countries opt for more decentralized structures others prefer to retain a centralization of powers. In this way some governments consider local features and national integration more than others, which ultimately influence the success of a port reform implementation. Nevertheless, the prime intent of governments is now to maximize the efficiency and performance of their domestic ports. This issue intends to examine the changed port governance environment in Brazil by determining how and why imposed port reforms of the Brazilian federal government have been affecting the overall performance of the national port system, over the last decades, using the Port of Santos as a sample upon an exploratory study. For that, the study will use a contingency theory-based framework – the Matching Framework - that views port performance as a function of the fit among the dimensions of external operating environment, strategy and structure of a port organization. In essence, the greater the fit among these dimensions the better the expected performance of a port will be, and vice-versa. Port managers, government officials and academics alike shall be interested in this document.